Penerapan Model Pembelajaran Think Pair Share Untuk Meningkatkan Hasil Belajar Bahasa Indonesia Kelas IV SD Katolik Stella Maris Girian - Ponge, Ivana Trimulia; Rindengan, Mersty E.; Dien, Stien A. (Peneliti.net, 2024)
This research aims to improve Indonesian language learning outcomes in the material of writing descriptive paragraphs by applying the Think Pair Share (TPS) learning model to fourth grade students at Stella Maris Girian Catholic Elementary School. This research method uses a Classroom Action Research (PTK) design using the Kemmis and Mc model. Taggart (Zainal Aqib, 2018) which consists of four stages, namely (1) Planning, (2) Implementation/Action, (3) Observation, (4) Reflection carried out in two cycles. Data collection techniques are carried out by means of observation, tests and documentation. The data analysis techniques used are qualitative and quantitative analysis. The results of learning Indonesian through the Think Pair Share (TPS) learning model for Class IV students at Stella Maris Girian Catholic Elementary School for cycle I were not optimal, of the 20 students who were given the test, only 35% of students scored above the minimum completeness criteria standard (KKM). ). In the second cycle, student learning outcomes showed a significant increase with a percentage of 83.75% of the total 20 students. Based on the results of the research conducted, it can be concluded that the application of the Think Pair Share (TPS) learning model can improve Indonesian language learning outcomes in the material of writing descriptive paragraphs for fourth grade students at Stella Maris Girian Catholic Elementary School